Robotic Sacrocolpopexy for Treatment of Apical Compartment Prolapse - Kwang Jin Ko; Kyu-Sung Lee (International Neurourology Journal, 2020)
Abdominal sacrocolpopexy is the gold-standard treatment for apical compartment prolapse, as it is more effective and durable than the transvaginal approach. In the current era of minimally invasive surgery, laparoscopic sacrocolpopexy techniques have been described, but have not gained popularity due to their complexity and steep learning curves. To overcome this problem, robotic sacrocolpopexy was introduced, and has shown equivalent outcomes and safety compared to open and laparoscopic sacrocolpopexy based on findings that have been accumulated over 15 years.